AKTIVITAS GOTONG-ROYONG DALAM MEMBANGUN RUMAH (TI’AYO) PADA MASYARAKAT DESA MOLIBAGU KECAMATAN BOLAANG UKI KABUPATEN BOLAANG MONGONDOW SELATAN - Tindo'o, Asman; Deeng, Djefry; Mulianti, Titiek (HOLISTIK, Journal Of Social and Culture, 2018)
Indonesians since is always been familiar with mutual cooperation activity, because basically the consisted community of humans intercourse with different interests in a certain life to achieve common aims in the work. The value of the activity of groups namely solidarity mutual cooperation attitude of people consider important the joint activity, loyalty group to perform a certain work by common interests or to members of the population. While a norm in mutual cooperation embodied in rules to obey and wanted to be involved in it. Indonesia community has the mention of the term mutual cooperation different. The Java community known with the spirit of holo pis kuntul baris; to the Maluku community known as pela gandhong; to the Tapanuli community known term dalihan-nan-tolu. While in Minahasa known with the term Mapalus, in Bolaang Mongondow called with the term Pogogutat and in Gorontalo known with the term Ambu. Mutual cooperation known the community in Molibagu Village Bolaang Uki Subdistrict South Bolaang Mongondow Regencies as ti’ayo. Help one another or ti’ayo in social activities building a house has been there from the first and it was attached to the Molibagu community. Until now ti’ayo come on still attached in the Molibagu community life, due to the existence of ti’ayo has become a sense of identity activities related to the community in terms of social, cultural and religious. The Molibagu community profoundly believe that everything relating to work can been resolved if it was with ti’ayo.Keywords: mutual cooperation, community, identity